Assessing the Effects of Vitamin D on Neural Network Function in Patients With Parkinson’s Disease by Measuring the Fraction Amplitude of Low-Frequency Fluctuation - Lv, Lingling; Zhang, Hainan; Tan, Xuling; Qin, Lixia; Peng, Xinke; Bai, Rongrong; Xiao, Qile; Tan, Changlian; Liao, Haiyan; Yan, Weiqian; Tan, Jieqiong; Tang, Beisha; et al. (Frontiers in Aging Neuroscience, 2021)
Background:Recently,many studies have shown that low vitamin D (VD) levels may be related to an increased risk of PD,but the underlying mechanisms remain unclear. Objective:To explore the relationship between PD and VD levels,as well as to analyze the effects of VD on spontaneous brain activity and explore the possible mechanism of its involvement in PD risk. Methods:In a cross-sectional study,we quantified the difference in VD levels between 330 PD patients and 209 healthy controls (HC) to explore the correlation between VD and PD risk.We also acquired rs-fMRI data from 46 PD patients and 21 HC.The PD patients were divided into three groups according to 25(OH)D level: PD patients with VD deficiency (PD+VDD),PD patients with VD insufficiency (PD+VDI),and PD patients with normal VD (PD+NVD),and its effect on spontaneous neuronal activity in the whole brain was analyzed by measuring the fraction amplitude of low-frequency fluctuation (fALFF). Results:Compared with HC,the PD patients had lower serum 25(OH)D levels (23.60±7.27vs.25.60±5.78,p<0.001).The 25(OH)D level may have a potential dose-dependent effect on the risk of PD (Ptrend=0.007). A high risk of PD was associated with VD deficiency (25(OH)D <20 ng/ mL,OR= 2.319),and the lowest quartile of 25(OH)D concentration was associated with a high risk of PD (OR=1.941).In the Rs-fMRI study,PD+VDD had wider brain regions with altered fALFF than other PD groups when compared with the corresponding HC groups.Both PD+VDD and PD+VDI showed higher fALFF in the cuneus,left precuneus,calcarine cortex and right lingual,lower fALFF in the left middle temporal gyrus.PD+VDD patients also showed higher fALFF in the left superior, middle and inferior frontal gyri,and the left precentral gyrus than HC. Among PD patients,there was only a statistically significant difference in fALFF between the PD+VDD and PD+NVD.And compared with PD+NVD group,PD+VDD patients exhibited higher fALFF in the left precentral and left postcentral gyrus,and the left inferior parietal lobule. Conclusion:These results demonstrate that PD patients had lower serum VD levels than HC,and VD may have a potential dose-dependent effect on PD risk.Lower serum VD levels can affect the spontaneous neuronal activity of default-mode network (DMN) and visual pathway neurons in PD patients,providing a possible mechanism for its effect on PD risk.